Sleep disturbance in patients with an implantable cardioverter defibrillator: Prevalence, predictors and impact on health status. (1st June 2018) - Habibović, M; Mudde, L; Pedersen, S S; Schoormans, D; Widdershoven, J; Denollet, J
Abstract: Background: Sleep disturbances are highly prevalent in patients with cardiac diseases and associated with poor health outcomes. However, little is known about sleep disturbance in patients with an implantable cardioverter defibrillator. Aims: We examined the prevalence and predictors of sleep disturbance and the impact on perceived health status in a Dutch cohort of implantable cardioverter defibrillator patients. Methods: Patients ( n =195) enrolled in the Web-based distress program for implantable cardioverter defibrillator patients (WEBCARE) trial completed questionnaires at the time of implantable cardioverter defibrillator implantation, three, six and 12 months afterwards. Sleep disturbance was assessed with the corresponding item #3 of the Patient Health Questionnaire 9. Results: At baseline, 67% ( n =130) reported sleep disturbance (cut off ≥1). One year later, the prevalence was 57% ( n =112). Younger age (odds ratio=0.96, 95% confidence interval 0.92–0.99; p =0.012) and high negative affectivity/low social inhibition (odds ratio=4.47, 95% confidence interval 1.52–13.17; p =0.007) were associated with sleep disturbance at 12 months in adjusted analyses. Sleep disturbance was not associated with health status at 12 months. Charlson Comorbidity Index, anxiety, Type D personality and high negative affectivity/low social inhibition were associated with impaired health status at follow-up. Conclusions: Sleep disturbance was highly prevalent in patients with an implantable cardioverter defibrillator. Younger age and high negative affectivity predicted sleep disturbance 12 months post-implantation independent of other demographic, clinical, intervention and psychological covariates. Sleep disturbance was not associated with impaired health status at the 12-month follow-up.